MiRNA-378 controls cell proliferation in rabbit umbilical cord mesenymal stem cells - Wang, H.; Zhao, Z.; Du, J.; Wang, T.; Yang, L.; Yu, H. (Cellular and Molecular Biology, 2016)
Mesenchymal stem cells (MSC) are known to have the ability to differentiate into various lineages of mesenchymal tissue. They are widely distributed in a variety of tissues in the body and are also present in the foetal environment. MicroRNAs (miRNAs) are a fundamental class of biological molecules that play a crucial role in development. In this study, microRNA-378 and its predicted target (Sufu, suppressor of fused homolog) were used to study proliferation of rabbit umbilical cord mesenymal stem cells, luciferase reporter assay was used to assess and confirm the binding sequence of 3"²untranslated region between microRNA-378 and Sufu. The results showed that miRNA-378 overexpression reduced Sufu gene, and promoted cell proliferation of rabbit umbilical cord mesenymal stem cells via cell viability and BrdU testing, which molecular mechanisms were down-regulation of apoptosis genes after miRNA-378 overexpression. In conclusion, our research shows that the microRNA-378 promoted the cell proliferation of rabbit umbilical cord mesenymal stem cells, and this mechanism was miRNA-378 reduced the expression of Sufu, increased cell proliferation.